Newly identified genomic regions conferring tolerance to trypanosomosis in Baoule cattle of Burkina Faso - CGIAR Research Program on Livestock (2021)
This paper reports genomic regions conferencing tolerance to trypanosomosis in Baoule cattle of Burkina Faso. Two genomic regions were identified in purebred Baoulé on chromosomes 16 and 24, containing the CFH, CRBN, TRNT1, IL5RA genes. This is the first report of an association between the CRBN gene and trypanosomiasis tolerance